2018
DOI: 10.1021/acs.molpharmaceut.8b00595
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic and Antagonistic Molecular Effects Mediated by the Feedback Loop of p53 and JNK between Saikosaponin D and SP600125 on Lung Cancer A549 Cells

Abstract: We jointly analyzed the changes in cell cycle arrest and distribution, the accumulation of subphase cells, apoptosis, and proliferation in A549 cells treated with Saikosaponin D (Ssd) and JNK inhibitor SP600125 alone or in combination. Our results indicated that cell cycle arrest at G0/G1, S, and G2/M phases was coupled with the accumulation of subG1, subS, and subG2 cells, corresponding to early apoptosis, DNA endoreplication, and later inhibitory proliferation, respectively. Analyzing the expression of 18 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…To validate the oxidative stress‐induced increase in miR‐34c is mediated by ROS‐JNK‐P53 pathway, we found that H 2 O 2 induced an increase in intracellular ROS production in HT‐22 cells by flow cytometry (FCM) assay (Figure a) and the JNK activation and P53 accumulation were induced by exogenous H 2 O 2 in a concentration‐dependent manner (Figure b). JNK has been reported to be implicated in P53 accumulation (Chen et al, ; Wu et al, ). Thus, the effect of JNK on P53 accumulation was determined by using of JNK inhibitor SP600125.…”
Section: Resultsmentioning
confidence: 99%
“…To validate the oxidative stress‐induced increase in miR‐34c is mediated by ROS‐JNK‐P53 pathway, we found that H 2 O 2 induced an increase in intracellular ROS production in HT‐22 cells by flow cytometry (FCM) assay (Figure a) and the JNK activation and P53 accumulation were induced by exogenous H 2 O 2 in a concentration‐dependent manner (Figure b). JNK has been reported to be implicated in P53 accumulation (Chen et al, ; Wu et al, ). Thus, the effect of JNK on P53 accumulation was determined by using of JNK inhibitor SP600125.…”
Section: Resultsmentioning
confidence: 99%
“…A review of the literature reveals the relevant situation downstream of JNK. For example, IL-2/sorafenib can affect tumor survival, growth and mobility through JNK-TAZ pathways (41), GPS1 can activate the c-Jun N-terminal kinase (JNK)/Jun pathway to affect breast cancer growth and migration (42), Saikosaponin D induced apoptosis via the activation of TGFα-JNK-p53 (43), Thymoquinone inhibits the metastasis through activation of JNK-p38 (44), JNK-ELK1 The pathway can also have an effect on the tumor (45). These are the pathways already known downstream of JNK, but there must be downstream pathways that have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Drugs related to cell cycle regulators act on the synergetic and antagonistic feedback loop formed by JNK / pJNK and p53 / p53. [16] Via WSSV-IE1, white spot syndrome virus (WSSV) combines with JNK and enhances JNK activation through self-phosphorylation, then establishes a positive feedback loop of JNK mediated by virus gene. [17] 3 JNK AND DEPRESSION…”
Section: Factors Affecting Jnkmentioning
confidence: 99%